Feasibility study of hybrid PV/diesel energy system at Institut Kemahiran Mara Johor Bahru - Omar, Mohd. Saifulizan (2015)
Nowadays, energy management wisdom is not measured by providing electricity solely. A well-established energy management characteristic should imposed a stable, reliable, sustainable, cost-wise, efficient and environmental health. One of the ideas to reinforce the need is to adopt renewable energy (RE) in the system i.e. solar, wind, tidal and etc. This work analyse the performance and feasibility of the hybrid PV/diesel energy system. The analyse will take account several constraints such as electricity consumption, trend of existing users, appropriate installation, return of investment (ROI) period, reduction to maximum power demand and total saving of bill payment to utility provider. The analysis will be carried out using well known software tool, HOMER software. Through the software, the technical feasibility is simulated and the optimal system configuration is determined. Three type of power system configurations are analysed; stand-alone system, hybrid PV/diesel without battery and hybrid PV/diesel with battery. Optimal energy system including energy production, cost of energy, net present cost and CO2 emission also explained in this paper.